Hot hands, cold feet? Investigating effects of interacting constraints on place kicking performance at the 2015 Rugby Union World Cup. Issue 10 (26th November 2018) - Pocock, Chris; Bezodis, Neil E.; Davids, Keith; North, Jamie S.
Abstract: Place kicks in Rugby Union present valuable opportunities to score points outside the spatiotemporal dynamics of open play but are executed under varying performance constraints. We analysed effects of specific task constraints and relevant contextual factors on place kick performance in the 2015 Rugby Union World Cup. Data were collected from television broadcasts for each place kick. In addition to kick outcomes, contextual factors, including time of the kick in the match, score margin at the time of the kick, and outcome of the kicker's previous kick, were recorded. Effects of spatial task constraints were analysed for each kick, using distance (m) and angle (°) of the kick to the goalposts. A binomial logistic regression model revealed that distance from, and angle to, the goalposts were significant predictors of place kick outcome. Furthermore, the success percentage of kickers who missed their previous kick was 7% lower than those who scored their previous kick. Place kick success percentage in the 10 minutes before half-time was 8% lower than the mean tournament success percentage, which was 75% (95% CI 71–78%). The highest kick success percentage was recorded when scores were level (83%; 95% CI 72–91%). Our data highlighted how subtle changes in task constraints and contextual factors can influence performance outcomes in elite performers in international competition. Fluctuations in place kick success suggested that individual constraints, such as thoughts, emotions and fatigue, induced during competition, could interact with perceptions to influence emergent performance behaviours.